Identification of Congestion Factors for Active Transportation and Demand Management: Case Study of Operations Data from Delaware Valley Regional Planning Commission. Issue 1 (January 2014) - Mize, Jonathan; Park, Seri; Matkowski, Laurie; West, Matthew
Traffic congestion is getting progressively worse in the United States, and transportation agencies are looking for ways to alleviate it. Extensive research has determined the need for the use of active transportation and demand management rather than the traditional technique of responding to congestion and traffic changes after an incident has occurred. For the full implementation of this new congestion management concept, a study featuring a comprehensive database review must be conducted to identify congestion factors as well as to estimate the likelihood of the occurrence of congestion. This paper introduces a pilot study that included an analysis to identify congestion contribution factors by examining several traffic data sources obtained in the Greater Philadelphia, Pennsylvania, area. The objectives of this study were to identify congestion factors and to provide insights as well as to support the metro-polilan planning organization's (MPO's) long-term regional planning. Weekly speed data per month in 2012 were analyzed. The study site of this paper, a segment of I-95, showed slightly higher recurrent congestion levels than national average values. For nonrecurrent congestion factors, crash occurrences and holidays were two major elements contributing to total congestion. The congestion mitigation measures examined were consistent with the MPO's transportation improvement plan and transportation operations master plan.